Correlation Between Self-Citation and Immediacy Index of Iranian Medical Scientific Journals Indexed in Scopus Citation Index Between 2005 and 2009 - Masoud Mohammadi; Alireza Noruzi; Hiwa Abdekhoda (Tehran University of Medical Sciences, 2012)
Background and Aim: Self-citation, as one of the limitations of citation analysis, unusually affects the ranking of journals. This study aims to evaluate the degree of relationship between self-citation and immediacy index correlation of Iranian medical journals indexed in Scopus Citation Index between 2005 and 2009. Materials and Methods: The method of the study is survey-descriptive in which citation analysis is used. The study included all Iran-based English medical journals indexed in Scopus database up to May 2009. The control list was prepared and its validity was confirmed. Data were collected by referring to Scopus website and publication review resources, and analyzed by statistical software and appropriate methods. Results: The findings showed that self-citation rate of journals was 29.64 percent, which comprised 14.43 percent of the total number of citations. There was a significant relationship (at the level of 0.01) between self-citation rate and immediacy index of journals (p = 0.591). Besides, Pearson correlation coefficient showed a significant relationship between the number of journals articles and the journals immediacy indexes excluding self-citation during the years of study. Conclusion: Self-citation has a direct effect on journals immediacy index; that is, an increase in the rate of self-citation causes an artificial increase in the journals immediacy index. On the other hand, immediacy index is affected by the number of journal articles. Therefore, the reduction or elimination of self-citation seems to be necessary for the journals and can put them in their right place.